ZAWARCIE MAŁŻEŃSTWA ‘LIBERORUM PROCREANDORUM CAUSA’ W PRAWIE RZYMSKIM - Niczyporuk, Piotr (Zeszyty Prawnicze, 2016)
MARRIAGE LIBERORUM PROCREANDORUM CAUSA IN ROMAN LAW Summary One of the chief purposes of the Roman institution of matrimony was procreation (liberorum procreandorum causa). There are numerous references in the sources to the institution of matrimony commending those citizens who marry in order to beget children. They are said to be living as Nature intended, since procreation secures the continuance of the family and tribe, especially as regards the passing down of the family name and estate to its heirs, and the guarantee that the religious rites (sacra familiaria and sacra gentilicia) will continue to be performed. Such observations were an expression of concern for the future of the Roman family. Marriage for the purpose of begetting progeny was regarded as sacrosanct, a religious duty: uxorem liberorum quaerundum causa ducere religiosum est. However, this applied only to children born of a iustum matrimonium – born in lawful wedlock to a couple who had entered an “approved marriage.” Roman citizens were encouraged and urged by the kings under the Monarchy, and even compelled by the censors, to marry and procreate. Augustus introduced legislation granting privileges to citizens who married, and special rights to families with a large number of children.